Workplace factors associated with job stress - Liu, Yuan (2006)
Job stress is an important issue in an organization. The objective of this research is to examine whether workplace factors ( intrinsic to the job, role in the organization, relationship at work, career development, and organization structure & climate) have a positive impact and significant on job stress, and also to examine whether the age and gender play moderate roles in the relationship between workplace and job stress. The literature review provides detail development of how these variables influence job stress. The resondents were based on a sample population. The questionnair were constructed out of extensive literature review. The hypotheses were tested using SPSSprogram of multiple regression and hierarchical regression. The research discovered that the workplace factors (intrinsic to the job, relationship at work, career development, organization structure and climate) have a positive impact and significant on job stress, the factor of role in the organization have a negative impact but no significant on job stress. Age and gender do not play moderate roles in all the relationship between workplace factors and job stress ..